Two important karst books written in less spoken languages - Kranjc, Andrej (Acta Carsologica, 2021)
Nowadays we are commonly used that important books, containing new data, new theories, new karst and cave descriptions, etc are published in English. This is why a publication in a less familiar language may be less important from the global point of view but may be much more important; of a key importance even, in the community of its language. Hence we are very glad to highlight the importance of two books, one in the (Brazilian) Portuguese which in fact is not at all less spoken language, and another one in the Croatian language; both authors are former students of the Karstology doctoral programme at the University of Nova Gorica (Slovenia).